The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1365-2842.2006.01652.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various Ca2+/PO concentrations of linseed‐based saliva substitutes on enamel in vitro

Abstract: Remineralization might be hampered by various polymers used in saliva substitutes. Thus, the present study evaluated the effects of various calcium and phosphate concentrations of linseed-based solutions on the mineral loss of pre-demineralized bovine enamel in vitro. A commercially available saliva substitute (Salinum) based on linseed was tested as well. Enamel specimens were prepared from bovine incisors and embedded in epoxy resin. One-third of each sample was covered with nail varnish (control of sound en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
(47 reference statements)
1
7
0
1
Order By: Relevance
“…It has been found that supersaturation of mucin-based saliva substitutes (self developed) with calcium phosphates may contribute to the remineralization of both demineralized enamel [27] and dentin [36]. Similar results have been reported for saliva substitutes based on linseed for bovine enamel and dentin [31,37] or carboxymethylcellulose (self developed) for bovine enamel [33]. However, carboxymethylcellulose-based saliva substitutes appeared to have only a little effect on remineralization of predemineralized dentin despite of saturation or supersaturation with calcium phosphates [38].…”
Section: Enamel and Dentin De-and Remineralizationsupporting
confidence: 58%
“…It has been found that supersaturation of mucin-based saliva substitutes (self developed) with calcium phosphates may contribute to the remineralization of both demineralized enamel [27] and dentin [36]. Similar results have been reported for saliva substitutes based on linseed for bovine enamel and dentin [31,37] or carboxymethylcellulose (self developed) for bovine enamel [33]. However, carboxymethylcellulose-based saliva substitutes appeared to have only a little effect on remineralization of predemineralized dentin despite of saturation or supersaturation with calcium phosphates [38].…”
Section: Enamel and Dentin De-and Remineralizationsupporting
confidence: 58%
“…Nevertheless, in this experiment, KH 2 PO 4 was used for comparing reasons with other studies investigating the remineralising properties of potential saliva substitutes. [8][9][10]29 Prospectively, high concentrated solutions with respect to phosphates should contain K 3 PO 4 , K 2 HPO 4 and it might be advisable to add appropriate buffer solutions.…”
Section: Discussionmentioning
confidence: 99%
“…For each block, sound, demineralized (DEM), and remineralized (REM) zones were then made on the same enamel surface as follows. First, one third of each block surface was covered with a nail varnish as described by Meyer-Lueckel et al [2006]. Subsurface lesions were then formed in a two-layer system of 8% methylcellulose gel (Metcel MC, Fluka, USA) and 0.1 M lactate buffer (pH 4.6) at 37 ° C for 14 days [ten Cate et al, 1996].…”
Section: Preparation Of Artificial Subsurface Lesionsmentioning
confidence: 99%